Comparison of Excellent Outcome of Laryngeal Mask Airway Insertion with Sevoflurane Versus Propofol as Induction Agent in Patients Undergoing Elective Surgeries under General Anesthesia - Sheikh Ziarat Ali, Kamran Javaid, Rahila Sharif, Rabia Zahid, Mehtab Tipu Chaudary, Fariha Aslam, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the excellent outcome of laryngeal mask airway insertion with sevoflurane versus propofol as induction agent in patients undergoing elective surgery under general anesthesia. Study Design: Randomized control trial. Study Setting: was conducted at Department of Anesthesia, Sir Ganga Ram Hospital, Lahore from November 2020 to April 2021. Materials and Methods: Using a random number table, patients were randomised into two groups at random. Group A was given up to 2.5 mg/kg of propofol intravenously while breathing 100% oxygen through a face mask. The anaesthetic circuit in Group B was primed for 30 seconds with Sevoflurane 8% IN N2O 50% and O2 (flow rate 8 liter/minute). Results: In our study the mean age of the patients was 33.89±9.64 years. 70% patients were males and 30% patients were females. The study results showed the excellent outcome was observed in 70.50% patients and it was not observed in 29.50% patients. Conclusion: Our study results concluded that the Sevoflurane is a safe and reliable anesthetic compared with currently available Propofol agent in patients undergoing elective surgery under general anesthesia.